Shot noise and scatter in the star formation efficiency as a source of 21-cm fluctuations. Issue 4 (16th February 2022) - Reis, Itamar; Barkana, Rennan; Fialkov, Anastasia
ABSTRACT: The 21-cm signal from cosmic dawn and the epoch of reionization probes the characteristics of the high redshift galaxy population. Many of the astrophysical properties of galaxies at high redshifts are currently unconstrained due to the lack of observations. This creates a vast space of possible astrophysical scenarios where the 21-cm signal needs to be modeled in order to plan for, and eventually fit, future observations. This is done with fast numerical methods which make simplifying approximations for the underlying physical processes. In this work, we quantify the effect of Poisson fluctuations and scatter in the star formation efficiency; while Poisson fluctuations are included in some works and not in others, scatter in the star formation efficiency is usually neglected, and all galaxies of a given mass are assumed to have the same properties. We show that both features can have a significant effect on the 21-cm power spectrum, most importantly in scenarios where the signal is dominated by massive galaxies. Scatter in the star formation efficiency does not simply enhance the effect of Poisson fluctuations; for example, we show that the power spectrum shape at cosmic dawn has a feature corresponding to the width of the galaxy brightness distribution. We also discuss some of the consequences for 21-cm imaging, and the signature of reduced correlation between the density and radiation fields.